2015
DOI: 10.1186/s12889-015-2471-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and perceptions towards polio immunization among residents of two highly affected regions of Pakistan

Abstract: BackgroundDespite the efforts of national and international organizations, polio has not been eradicated from Pakistan. The prevalence of polio in Pakistan is exceptional in global context. Quetta and Peshawar divisions are amongst the most affected regions hit by polio in Pakistan. This study was carried out to assess the knowledge, attitudes and perceptions towards polio immunization among residents of Quetta and Peshawar divisions in Pakistan.MethodsA descriptive, cross-sectional study involving 768 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 18 publications
6
74
0
3
Order By: Relevance
“…According to the literature, the causes of vaccine hesitancy among parents include lack of confidence in vaccine ingredients, healthcare system, media, and pharmaceutical industry (Dubé et al, 2018; Gilkey et al, 2014). Based on the availability of excessive vaccines (Kettunen et al, 2017) and lack of information (Khan et al, 2015), sceptics often believe that vaccines cause severe complications and certain diseases (Maglione et al, 2014). According to Larson et al (2015), factors influencing vaccination at the individual level include the following: (a) experiences related to vaccination; (b) beliefs and attitudes about health and prevention; (c) knowledge and awareness; (d) trust in the healthcare system and service providers as well as personal experience; (e) risk/benefit (perceived); and (f) social norms concerning vaccines being necessary/harmful.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the causes of vaccine hesitancy among parents include lack of confidence in vaccine ingredients, healthcare system, media, and pharmaceutical industry (Dubé et al, 2018; Gilkey et al, 2014). Based on the availability of excessive vaccines (Kettunen et al, 2017) and lack of information (Khan et al, 2015), sceptics often believe that vaccines cause severe complications and certain diseases (Maglione et al, 2014). According to Larson et al (2015), factors influencing vaccination at the individual level include the following: (a) experiences related to vaccination; (b) beliefs and attitudes about health and prevention; (c) knowledge and awareness; (d) trust in the healthcare system and service providers as well as personal experience; (e) risk/benefit (perceived); and (f) social norms concerning vaccines being necessary/harmful.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed 93.6% of the mothers had satisfactory knowledge which is very high compared to the study done by Khan et al, where only 38.8% of the participants exhibited good knowledge about polio. 8 About 73.64% of mothers knew paralysis of lower limb as the symptom, which is high (56%) compared to study conducted in rural area of Kannur near Anjarakandy and in highly affected areas of Pakistan (58.4%). 7,8 About 87.73% of mothers were aware of IPV in the present study, which is very high compared to study done in south east Nigeria (47%).…”
Section: Discussionmentioning
confidence: 94%
“…8 About 73.64% of mothers knew paralysis of lower limb as the symptom, which is high (56%) compared to study conducted in rural area of Kannur near Anjarakandy and in highly affected areas of Pakistan (58.4%). 7,8 About 87.73% of mothers were aware of IPV in the present study, which is very high compared to study done in south east Nigeria (47%). 9 Eighty seven percent of the mothers were aware that the route of polio vaccine as both oral and injection but in a study done by Sarada et al, 65.3% and 11.3% of the mothers told that the route of administration of polio vaccine as oral drops and as injection respectively.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, service providers in clinics do not emphasize the importance of immunization [34]. Religious beliefs and lack of knowledge about the benefits of the vaccines still dictate many pockets of this highly diverse and populated country [35]. Targeted community awareness programs, a robust surveillance network, and engagement with the dominant religious entities can help to root out the issue [36,37].…”
Section: Community Perceptions and Behaviorsmentioning
confidence: 99%